JMPB 2019
DOI: 10.7176/jmpb/54-20
|View full text |Cite
|
Sign up to set email alerts
|

Role of Magnesium Sulphate in Newborns With Birth Asphyxia.

Abstract: Background; Birth asphyxia is a leading cause of mortality and morbidity in neonates in developing countries, with an incidence of 100-250/1000 live births compared to 5-10/1000 live births in the developed world. It remains a significant cause of loss of life and adverse developmental outcome. Objective; To compare magnesium sulphate therapy versus placebo in control of fits among newborns admitted with birth asphyxia along with fits at a tertiary care hospital. Material and Methods; All the study (n=260) par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…Other searching identified a further 13 records to screen; we excluded two. Therefore, we included 29 studies (reported across 35 references) 29–63 . A study flow diagram is shown in Figure S1; Appendix S2 lists the records excluded at the full‐text screening.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Other searching identified a further 13 records to screen; we excluded two. Therefore, we included 29 studies (reported across 35 references) 29–63 . A study flow diagram is shown in Figure S1; Appendix S2 lists the records excluded at the full‐text screening.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 29 studies included, 25 were RCTs, 29–47, 49–51, 53–61 and four were non‐RCTs (two were non‐randomized trials and two were non‐concurrent cohort studies); 48, 52, 62, 63 three were available as abstracts only 33, 40, 50 . Twenty‐three studies were conducted exclusively in LMICs (nine in India; 31, 32, 35, 46, 47, 51, 58, 60, 62 eight in Pakistan; 30, 42, 43, 49, 56, 57, 59, 61 three in Egypt; 29, 33, 44 one each in Bangladesh, 40 Nigeria, 52 and Albania 50 ); five in HICs (two in Poland; 39, 63 one each in the Netherlands 36 and Japan; 41 one across five European centres 48 ); and one across mixed settings (Qatar, Turkey, Saudi Arabia, Egypt, Malaysia, and the United Arab Emirates 55 ). Where reported, study commencement dates ranged from 1995 36 to 2021 43, 57 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations